2013
DOI: 10.1532/hsf98.20121038
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Outcomes of Pedicled Bilateral Internal Mammary Artery Use in Diabetic and Nondiabetic Patients Undergoing Off-Pump Coronary Artery Bypass Grafting: Single-Surgeon, Single-Center Experience

Abstract: Pedicled BIMA use is associated with comparable incidences of sternal wound complications and other outcomes in diabetic patients and nondiabetic patients. Strict perioperative glycemic control, adherence to meticulous closure technique, and postoperative management of surgical wounds can make pedicled BIMA use a default strategy for diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Nishi et al showed that sternal microcirculation damage after pedicled and skeletonized internal mammary artery harvesting was similar, indicating that the latter technique may not be advantageous. 29 However, we believe that preoperative selection bias remains a confounding factor in the interpretation of results associated with skeletonized harvesting and the use of BIMA grafts, and that more randomized studies are needed in the future. In addition, many previous studies also showed that perioperative control of blood glucose could lower the risk of SWI.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nishi et al showed that sternal microcirculation damage after pedicled and skeletonized internal mammary artery harvesting was similar, indicating that the latter technique may not be advantageous. 29 However, we believe that preoperative selection bias remains a confounding factor in the interpretation of results associated with skeletonized harvesting and the use of BIMA grafts, and that more randomized studies are needed in the future. In addition, many previous studies also showed that perioperative control of blood glucose could lower the risk of SWI.…”
Section: Discussionmentioning
confidence: 98%
“…22 In the present analysis, we found that BIMA grafting was associated with a significantly lower risk of postoperative hospital all-cause mortality than SIMA grafting in diabetic populations, which is consistent with previous studies. 29,30 The use of BIMA appeared to be advantageous in diabetic patients because of the diffuse nature of diabetic coronary lesions and the small caliber of the coronary arteries. 31 The internal mammary arteries were proved to enhance the production of endothelium-derived nitric oxide, 32 which or SIMA.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…We analyzed the 10-year outcomes of OPCAB multivessel arterial grafting (16) as well as sequential grafting (17). Outcomes of OPCAB surgery were also compared with those of onpump CABG in octogenarians (18) and diabetics (19). Most importantly, we demonstrated that at long-term follow-up, OPCAB remains a safe and effective myocardial revascularization strategy with no adverse impact on survival or freedom from reintervention (20).…”
Section: Outcomes From the Maintenance Phasementioning
confidence: 99%
“…hospital continues to offer OPCAB surgery as a valid alternative to conventional CABG. The surgeons, at this institution of national and international reputation, have developed a high level of expertise with this technique enabling them to offer this strategy to a large number of patients with increasing comorbidities and complexity of coronary lesions with excellent outcomes (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(16)(17)(18)(19)(20). More importantly, the OPCAB surgeons at Harefield hospital have not lost their focus in regard to the goals of surgical coronary revascularization.…”
Section: Outcomes From the Maintenance Phasementioning
confidence: 99%
“…We have recently described our standardized sternotomy wound care bundle in detail [ 4 ]. We clip all the side branches during ITA harvest and use the point haemostasis technique to minimize leaving charred tissue on the inside of the chest wall, which could potentially act as a culture medium for microbes.…”
mentioning
confidence: 99%